Analysis of compact H-shaped microstrip antenna - Ansari J.A.; Dubey S.K.; Singh P.; Khan R.U.; Vishvakarma B.R. (My University, 2025)
Analysis of H-shaped patch is carried out using equivalent circuit model. It is found that the antenna exhibits dual resonance behavior which is very sensitive to the dimensions of the notch. The theoretical results of proposed method are compared with experimental and theoretical result reported earlier using FDTD method. Comparison with other reported results justify the veracity of the proposed method. © 2008 Wiley Periodicals, Inc.